Transformation of Self-Directed Learning Abilities Among Distance Learner - Annuar, Nursyamilah; Shaari, Roziana (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The results of increase in knowledge, fast-paced technology and changes in working environment leads adult as learners to be more competitive. As potential human resources, adult learners should cultivate their self-directed learning ability in order to be more competitive. However, adult learners still face great difficulty in gaining new knowledge as todays adult learners are still very much lack of readiness to self-direct in learning. It is important for adult learners who pursue distance learning to possess self-directed learning ability. Therefore, one of the options for these adult learners to develop their self-directed learning ability is through the practice in distance learning. This learning provides a platform for adult learners to planning, implementing and evaluating their own learning activities.